Biological Activities and Application of Marine Polysaccharides 2017
DOI: 10.5772/65588
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan as Source for Pesticide Formulations

Abstract: Late blight and wilt caused by the oomycete, Phytophthora infestans, and the fungus, Fusarium solani f. sp. eumartii, respectively, are severe diseases in Solanaceae crops worldwide. Although traditional approaches to control plant diseases have mainly relied on toxic chemical compounds, current studies are focused to identify more sustainable options. Finding alternatives, a low molecular weight chitosan (LMWCh) obtained from biomass of Argentine Sea's crustaceans was assayed. In an attempt to characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In fact, based on Qiu et al () findings, a coating with chitosan at 2.5 and 10.0 g/L is sufficient to limit the decay of green asparagus induced by Fusarium concentricum . Also, according to Ippólito et al (), the effectiveness of this antimicrobial compound against Phytophthora infestans and Fusarium eumartii , based on chitosan IC50 value (the concentration needed to inhibit half of the maximum spore germination), is estimated at 0.1 µg/ml and 130 µg/ml, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, based on Qiu et al () findings, a coating with chitosan at 2.5 and 10.0 g/L is sufficient to limit the decay of green asparagus induced by Fusarium concentricum . Also, according to Ippólito et al (), the effectiveness of this antimicrobial compound against Phytophthora infestans and Fusarium eumartii , based on chitosan IC50 value (the concentration needed to inhibit half of the maximum spore germination), is estimated at 0.1 µg/ml and 130 µg/ml, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently, first transcriptome studies using an RNAseq approach have been reported in chitosan-treated strawberry (Landi et al, 2017) and avocado (Xoca-Orozco et al, 2017) fruits. While a protective effect of chitosan treatment on potato, e.g., against Phytophthora infestans (O'Herlihy et al, 2003;Chang and Kim, 2012;Ippoĺito et al, 2017) or potato virus X (Chirkov et al, 2001) has been described, no such transcriptomic study has been conducted in potato yet. However, several transcriptome analyses on potato have been published, e.g., describing gene expression under drought stress (Gong et al, 2015) and other abiotic and biotic stresses (Massa et al, 2013), mostly based on the reference data for the potato transcriptome by Massa et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan has well documented antifungal activity, and in earlier research, low molecular weight chitosan alone or in combination with the commercial mancozeb controlled the spore formation for late blight and wilt caused by the pathogens P. infestans and Fusarium solani f. sp. eumartii , respectively [ 44 ]. Increasing the concentration of the nanofungicide provided better results, and was comparable to non-nanoform results.…”
Section: Resultsmentioning
confidence: 99%